Determinants of visual inspection with acetic acid (VIA) coverage among women of reproductive age for early cervical cancer detection (KHD-Production, 2025)
Cervical cancer remains a significant public health problem and a leading cause of death among women in low- and middle-income countries, including Indonesia. Visual Inspection with Acetic Acid (VIA) is a cost-effective screening method, yet its effectiveness varies depending on individual, social, and institutional factors. This study aimed to analyze the relationship between demographic, psychosocial, and support-related factors and the effectiveness of VIA examination among women of reproductive age (WRA) at a private midwife practice in Tangerang Regency, Indonesia. A cross-sectional design was used involving 91 respondents selected through purposive sampling. Data were collected using a validated questionnaire and clinical VIA records. Bivariate analysis was conducted using the Chi-square test, followed by multivariate logistic regression to identify dominant predictors of ineffective VIA examination. The bivariate analysis showed significant associations between VIA examination effectiveness and age (p = 0.001), education level (p = 0.009), knowledge (p = 0.015), family support (p = 0.028), and health worker support (p = 0.042). Multivariate analysis identified age as the most dominant predictor, with women aged over 35 years being 6.2 times more likely to experience ineffective VIA examination (OR = 6.21; 95% CI = 2.15–17.89). Age and psychosocial factors significantly influence the effectiveness of VIA screening. Targeted health education and enhanced support from families and midwives are crucial to improving VIA performance and participation rates among women of reproductive age. Strengthening midwife-led community interventions may improve early detection outcomes of cervical cancer in Indonesia.